STRATEGI KNOWLEDGE MANAGEMENT PADA PT PLN (PERSERO) UNIT INDUK PEMBANGUNAN SUMATERA BAGIAN UTARA - Rosa Pangaribuan, Nani; Lumbanraja, Prihatin; Yunita Aritonang, Evawany (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
In the modern business era, companies are faced with the need for knowledge workers who ultimately produce innovations to support work and increase company sustainability. The company's strategy for human resource management is important. The implementation of Knowledge Management (KM) is one of the human capital readiness and organizational readiness strategies in the performance targets of PT PLN (Persero) North Sumatra Development Parent Unit (PLN UIP SBU) to improve the ability of selected talents to match the competencies needed by PLN, so that they can make a maximum contribution in their position. KM implementation has been running for almost 15 years, but employee interest in KM implementation is still low because many employees do not understand KM and have not benefited from it. KM has not been running in accordance with the provisions of PT PLN (Persero). This research uses descriptive qualitative methods with data collection methods through observation, in-depth interviews and focus group discussions. The results of this study indicate that leaders are the main key driving the successful implementation of knowledge management at PT PLN (Persero) North Sumatra Development Parent Unit. Innovation reflects the success of KM implementation. Updating the knowledge management system technology infrastructure, evaluating and assessing the maturity level of KM implementation is very important to improve KM implementation. This research provides alternative strategies for better KM implementation, namely collaboration between functions to carry out KM refreshment, encourage innovation work competitions, utilization of pre-retirement employees, workshops and external certification, and reporting KM implementation to the PLN Central Team to get evaluation and feedback.